2020
DOI: 10.1186/s12978-020-00979-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perspectives, preferences and needs of a telemonitoring program for women at high risk for preeclampsia in a tertiary health facility of Karachi: a qualitative study protocol

Abstract: Background In Pakistan, deaths from preeclampsia/eclampsia (PE/E) represent one-third of maternal deaths reported at tertiary care hospitals. To reduce the morbidity and mortality associated with PE/E, an accessible strategy is to support pregnant women at high risk for preeclampsia (HRPE) by closely monitoring their blood pressures at home (i.e., telemonitoring) for the earliest signs of preeclampsia. This could lead to the earliest possible detection of high blood pressure, resulting in early intervention su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Health promotion, illness prevention, diagnosis, treatment, monitoring, and assistance of health services were highlighted as the six primary aims of mobile interventions. For example, 51.5 percent of mHealth apps were developed to assist healthcare services, while 33.3 percent were developed to monitor healthcare services [14][15][16].…”
Section: Empirical Evidencesmentioning
confidence: 99%
“…Health promotion, illness prevention, diagnosis, treatment, monitoring, and assistance of health services were highlighted as the six primary aims of mobile interventions. For example, 51.5 percent of mHealth apps were developed to assist healthcare services, while 33.3 percent were developed to monitor healthcare services [14][15][16].…”
Section: Empirical Evidencesmentioning
confidence: 99%
“…The articles reported varying eligibility criteria for selecting high-risk pregnant women for different DHIs. Some articles selected high-risk pregnant women based on the NICE guidelines, 20 specific age groups such as pregnant women aged 15–49 years, 22 while a few articles selected pregnant women based on their residential area such as women living in study catchment area, 23 permanent resident of the particular area, or non-resident who delivered in the study area. 18 Most DHIs collected blood pressure, heart rate and pulse oximetry, with some innovations collecting data on additional indicators such as demographic data, haemoglobin, urine dipstick test to detect proteinuria and glucose, other urinary markers and PE symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 19 articles were identified after the full-text screening that met the inclusion criteria for this review. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Fifty-three articles were excluded for the following reasons: (1) the study was not reported in the English language; (2) the publication did not talk about pregnant women at HRPE; (3) the research did not include any of the DHIs; (4) the publication was a conference abstract, review, editorial, commentary or (5) the study implemented the DHIs for pregnant women at HRPE in high-income countries. The study selection procedure was recorded according to the PRISMA-ScR flow diagram (figure 1).…”
Section: Selection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare providers play a key role in adapting women with preeclampsia to hospital settings, connecting with family members, and connecting with people who can provide them with information (40). As pointed out in the studies, when information and counselling about their disorder is given to inpatient women who are in the hospital for preeclampsia treatment, their anxiety levels decrease.…”
Section: Discussionmentioning
confidence: 99%